2013
DOI: 10.1021/jz402165b
|View full text |Cite
|
Sign up to set email alerts
|

Energy Band Alignment between Anatase and Rutile TiO2

Abstract: Using photoelectron spectroscopy, the interface formation of anatase and rutile TiO 2 with RuO 2 and tin-doped indium oxide (ITO) is studied. It is consistently found that the valence band maximum of rutile is 0.7 ± 0.1 eV above that of anatase. The alignment is confirmed by electronic structure calculations, which further show that the alignment is related to the splitting of the energy bands formed by the O 2p z lone-pair orbitals. The alignment can explain the different electron concentrations in doped anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
155
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(181 citation statements)
references
References 53 publications
24
155
1
Order By: Relevance
“…The spectro/photo/ electrochemical measurements by Jankulovska et al [8] confirmed the positive offset of 0.2 eV between the CBMs of anatase and rutile, and other measurements, like EPR [10], photoluminescence [11], photocatalytic Ag + reduction [12,13] and H 2 evolution [14] on mixed-phase particles, also reported the CBM of anatase being higher than that of rutile. In contrast to these works, all photoelectron spectroscopy (PES) studies -carried out on layers in electrical contact and in a vacuum environment -seem to agree that the CBM of rutile is lying higher [15][16][17]. The popular material in photocatalysis, Degussa (Evonik) P25 contains anatase/rutile mixed-phase particles, and there is a reasonable consensus that the enhanced photocatalytic activity is driven by exciton dissociation across the anatase/rutile interface, for which the CBM offset provides the necessary driving force.…”
Section: Introductionmentioning
confidence: 69%
“…The spectro/photo/ electrochemical measurements by Jankulovska et al [8] confirmed the positive offset of 0.2 eV between the CBMs of anatase and rutile, and other measurements, like EPR [10], photoluminescence [11], photocatalytic Ag + reduction [12,13] and H 2 evolution [14] on mixed-phase particles, also reported the CBM of anatase being higher than that of rutile. In contrast to these works, all photoelectron spectroscopy (PES) studies -carried out on layers in electrical contact and in a vacuum environment -seem to agree that the CBM of rutile is lying higher [15][16][17]. The popular material in photocatalysis, Degussa (Evonik) P25 contains anatase/rutile mixed-phase particles, and there is a reasonable consensus that the enhanced photocatalytic activity is driven by exciton dissociation across the anatase/rutile interface, for which the CBM offset provides the necessary driving force.…”
Section: Introductionmentioning
confidence: 69%
“…Such significant energy spaces between corresponding band edges for two TiO2 phases also was observed by experiments. The polycrystalline anatase thin films and rutile single crystals prepared by Pfeifer et al shows that the VBM (CBM) of rutile is 0.7 (0.5) eV above that of anatase according to the photoelectron spectroscopy analysis 47 .…”
Section: Tablementioning
confidence: 99%
“…2. It is known that photocatalytic efficiency of TiO 2 is substantially increased in the sample containing both crystal phases (anatase and rutile) compared to single crystal sample [29]. Further increase of calcination temperature to 800 • C induced decrease of photocatalytic efficiency which is still higher compared to the as prepared titania nanotubes and samples calcined at temperatures lower than 700 • C. Such decrease in photocatalytic efficiency could be explained by the higher degree of particle agglomeration.…”
Section: Resultsmentioning
confidence: 98%
“…Considering degradation rates of selected herbicides, presented in Table 3, it could be concluded that there were no significant differences in photocatalytic activity of calcined sample. But, the overall increase in their photocatalytic activity in comparison to as prepared nanotubes is mainly the consequence of their generally higher crystallinity and existence of anatase and rutile phases (95%: 5%), which is a favorable condition (prerequisite) for the efficient photocatalytic degradation process on the surface of TiO 2 nanoparticles [29]. Taking into account negative electrostatic potential of studied molecules and the pH value of TNT 700 dispersions (7.2-7.8), it is clear that deprotonated surface of nanocrystals does not contribute significantly to increased efficiency of degradation process.…”
Section: Resultsmentioning
confidence: 99%